The Contemporary Multifamily Architecture in Lima Blocks: the Case of Magdalena del Mar - Fleischman-Nessim, Moris (Universidad de Lima. Carrera de Arquitectura, 2017)
The research article analyzes the difficulties of design on several multifamily buildings under construction in Lima. Nowadays, the dimensions of the lots, the regulations in Lima and the real estate pressure have lead to some kinds of buildings with a persistent configuration. We try to reveal someof the essential characteristics which are deeply re-categorizing many of the traditional urban tissues of the city, such is the case of the district of Magdalena del Mar. The methodology is conceptually based on a typological understanding of housing, and it is operatively based on the use of orthographic drawing as an analysis tool. Finally, we consider whether these contingencies allow the projection of buildings with a collective idea of the city. The research leaves open the possibility to use its conclusions in the feedback of the municipal urban parameters.